2021
DOI: 10.33215/sjom.v4i1.513
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Emotional and Spiritual Intelligence on Job Satisfaction and Turnover Intention

Abstract: Purpose- Several critical factors contribute to employees' satisfaction or an attempt to stay with an organization. This paper aimed to explore the impact of emotional and spiritual intelligence on job satisfaction and turnover intention among employees in the telecommunication companies in Ghana. Design/Methodology- A cross-section research design approach was adopted. A questionnaire was used to gather data from employees in MTN, Vodafone, and Airtel-Tigo in the Kumasi Metropolis Ghana through a simple rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The more emotional intelligence increases, the job satisfaction will increase. This is in line with the findings of Zulaikha & Parmin (2019), Rahmawati (2022), Korankye and Amakyewaa (2021), which explain that emotional intelligence has a positive and significant effect on job satisfaction.…”
Section: Figure 1 Path Analysis Modelsupporting
confidence: 92%
“…The more emotional intelligence increases, the job satisfaction will increase. This is in line with the findings of Zulaikha & Parmin (2019), Rahmawati (2022), Korankye and Amakyewaa (2021), which explain that emotional intelligence has a positive and significant effect on job satisfaction.…”
Section: Figure 1 Path Analysis Modelsupporting
confidence: 92%
“…It is not the cash or the incidental advantages yet the emotions and feelings employees get from their work (Bachri & Solekah, 2021;Spector, 1985). In contrast, the turnover intention is characterised as the intention of workers to find employment elsewhere (Alola, Olugbade, Avci & Ozturen, 2019;Korankye & Amakyewaa, 2021). A study conducted by Akinwale and George (2020) with a few selected Nigerian banks, such as Access, UBA, and GTB in Nigeria, found that job satisfaction promotes the intention to leave among lower employees working in the banks.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…A cursory search on the predictive role of SI on TI shows that two research evidences exist (Korankye and Amakyewaa, 2021; Ghaderzadeh, 2020) and both reveal significant predictive effect. This study contributes to the debate by proposing mechanisms that demonstrate how SI predicts TI through sanctification of work (SoW) and job satisfaction (JS).…”
Section: Introductionmentioning
confidence: 99%